Hardiness in Family Caregivers During Caring From Persons With Alzheimer's Disease: A Deductive Content Analysis Study - Hosseini, Lida; Sharif Nia, Hamid; Ashghali Farahani, Mansoureh (Frontiers in Psychiatry, 2022)
Objective: This study was designed to describe the experiences of family Caregivers' hardiness in caring for Alzheimer’s Patients. Methods. The deductive content analysis method was performed between April 2020 and February 2021 in one of the teaching hospitals in Iran. Fourteen family caregivers of Alzheimer’s patientswere selected using purposive and snowballing sampling and the data were collected by semi-structured interviews. After that, data were analyzed using Elo and Kingas steps. Results. The results of this study showed that based on the experiences of family caregivers, the family caregivers' hardiness in caring for Alzheimer’s patients is a feature of cognitive ability to deal with stressful care situations and consists of five dimensions of commitment, control, challenge, communication and culture with 22 generic categories that they were nested into this five dimension. Conclusion. Family caregivers’ hardiness is a trait related to the individual and environmental factors, and the prevailing social and cultural conditions affect the individual's perception and experience of hardship and threats, as well as his/her understanding of protective factors and how to use them. Therefore, hardiness should not be interpreted as a simple approach regardless of culture.